Sound the trumpet : the United States and human rights promotion - Haas, Lawrence J. (Rowman & Littlefield Publishers, 2012)
In Sound the Trumpet, Lawrence J. Haas examines the effort by advance freedom and democracy around the world. Haas argues forcefully that, for all of our missed opportunities and tragic errors, the world is a better place because of our efforts.